Accuracy of tumor size measurement: comparison of B-mode ultrasound, strain elastography, and 2D and 3D shear wave elastography with histopathological lesion size. (April 2019) - Farrokh, André; Maass, Nicolai; Treu, Linn; Heilmann, Thorsten; Schäfer, Fritz KW
Background: Predicting the exact extent of a breast tumor is of great importance for oncologic treatment strategies. Different types of elastography can be used as new tools for measuring lesion size. Purpose: To provide evidence regarding the accuracy of tumor size measurement of strain elastography (SE), two-dimensional (2D) and three-dimensional (3D) shear wave elastography (SWE), and conventional B-image ultrasound. Material and Methods: In this prospective study, the diameter of 105 malignant breast lesions was measured by SE, 2D and 3D SWE, and B-mode ultrasound. The histopathological lesion size was compared to all imaging-based measuring methods. Results: The mean lesion size of all breast carcinomas was 1.54 cm. B-mode ultrasound underestimates breast cancer size in 65.7 % of all cases in this study ( P  < 0.0001). Mean lesion size was more accurately determined by SE, 2D and 3D SWE compared to B-mode ultrasound. Absolute differences between measured and actual lesion are smaller for B-mode ultrasound (0.26 cm) than for SE (0.41 cm) and 2D and 3D SWE (0.41 cm and 0.44 cm, respectively). Conclusion: B-mode ultrasound allows more accurate lesion size measurement than SE and 2D or 3D SWE but has a significantly higher risk of underestimating tumor size which could lead to incomplete margins during surgery. 3D SWE was not superior to 2D SWE or SE but by trend more precise in predicting the size of invasive lobular carcinoma.